A comparison of four established GFR formulas to estimate measured GFR and changes in GFR in adult kidney transplant recipients. (1st July 2022) - Trans, Josefine Gammelgaard; Krogstrup, Nicoline V.; Oltean, Mihai; Jespersen, Bente; Nielsen, Marie Bodilsen; Birn, Henrik
Abstract: The accurate assessment of glomerular filtration rate (GFR) is important in the follow-up of kidney transplant recipients in order to identify graft dysfunction. A number of formulas have been proposed to calculate GFR from endogenous plasma markers such as creatinine or cystatin C since measuring GFR using exogenous markers is troublesome. This study compares and evaluates the ability of four different GFR formulas to estimate kidney graft function and to detect changes in GFR in kidney transplant recipients. The study included patients from the prospective, multicenter CONTEXT trial in kidney transplant recipients. GFR was measured using plasma clearance of 51 Cr-EDTA and estimated using the MDRD, CKD-EPI Creatinine, CKD-EPI Cystatin C and CKD-EPI Cystatin C + Creatinine equations at three ( n = 83) and twelve ( n = 65) months post-transplantation. For each formula mean bias, precision, and accuracy were evaluated. The MDRD equation had the lowest mean bias (0.2 ml/min/1.73 m 2 ), whereas the CKD-EPI Cystatin C + Creatinine equation had the highest precision (8 ml/min/1.73 m 2 ). Accuracy at three months were similar for all equations (P30 > 80%) except for the CKD-EPI Cystatin C equation, which performed poorer (P30 = 55%). None of the formulas evaluated avoided misclassification of changes in GFR. The most optimal combination of precision and accuracy suggests the use of CKD-EPI Creatinine + Cystatin C equation in kidney transplant recipients.